1993
DOI: 10.1288/00005537-199301000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Implications of positive surgical margins

Abstract: The recently concluded Head and Neck Intergroup trial tested the addition of three courses of cis-platinum containing chemotherapy to standard treatment of surgery and postoperative radiotherapy for patients with advanced operable squamous cell carcinoma of the head and neck. Only patients with negative surgical margins were eligible for the trial. One hundred twelve patients with positive surgical margins were dropped from the trial but continued to be followed. These patients received a variety of treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 8 publications
5
46
0
Order By: Relevance
“…Consequently, in the present study, all pathology reports were reviewed and resection margins were considered as positive in cases where invasive carcinoma was present at the border of resection on permanent pathology sections. The incidence of positive resection margins in the head and neck area varies from 3% to 60% [24]. Such a significant variation could be the result of a different interpretation of tumor free margins, as well as a high percentage of locally advanced carcinomas in certain reports [10].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…Consequently, in the present study, all pathology reports were reviewed and resection margins were considered as positive in cases where invasive carcinoma was present at the border of resection on permanent pathology sections. The incidence of positive resection margins in the head and neck area varies from 3% to 60% [24]. Such a significant variation could be the result of a different interpretation of tumor free margins, as well as a high percentage of locally advanced carcinomas in certain reports [10].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…It is well accepted that patients demonstrating a positive surgical margin (dysplastic/cancerous epithelium within the surgical margin) have a higher incidence of local recurrence. [3][4][5][6] Previously we showed that vital staining with iodine solution could delineate the precise area of the dysplastic epithelium. 8 The dysplastic and cancerous epithelium was not stained with iodine solution, whereas the surrounding normal non-keratinized mucosa was stained brown-black.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] It has been shown that failure to achieve a clear surgical margin results in increased risk of local recurrence and a subsequently reduced chance of survival. [3][4][5][6] In oral cancer surgery, intraoperative margin assessment is usually performed using direct inspection and palpation and/or frozen section analysis; however, these methods have limitations in ensuring the complete resection of tumor and mucosal epithelium at a risk of malignancy. Vital staining with iodine solution has been employed intra-operatively with success in determining the extent and precise border of the cancerous/dysplastic epithelium, ensuring complete resection of the tumor at the mucosal surface.…”
Section: Introductionmentioning
confidence: 99%
“…Cases of positive margins in the specimen, but negative margins in the patient, were eligible for randomization and classified as ''close'' (ie, < 5 mm). 3 Patient margins that contained disease rendered that patient ineligible for the subsequent randomized phase of the study. However, these patients were monitored for disease outcome, 4 and this information was used for this re-analysis, even though therapy was not dictated by the protocol.…”
Section: Methodsmentioning
confidence: 99%